2007
DOI: 10.1021/ic701313h
|View full text |Cite
|
Sign up to set email alerts
|

Heats of Formation of Krypton Fluorides and Stability Predictions for KrF4and KrF6from High Level Electronic Structure Calculations

Abstract: Atomization energies at 0 K and heats of formation at 0 and 298 K are predicted for KrF+, KrF-, KrF2, KrF3+, KrF4, KrF5+, and KrF6 from coupled-cluster theory (CCSD(T)) calculations with effective core potential correlation-consistent basis sets for krypton. To achieve near chemical accuracy (+/-1 kcal/mol), three corrections were added to the complete basis set binding energies based on frozen core coupled-cluster theory energies: a correction for core-valence effects, a correction for scalar relativistic eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
13
0
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 37 publications
5
13
0
1
Order By: Relevance
“…In contrast, the experimental enthalpy of formation at ambient pressure is slightly positive (0.21 eV/atom [16]). This value was well reproduced with rigorous coupled-cluster calculations of Dixon et al [55]. In our previous study, we found that the Perdew-Burke-Ernzerhof (PBE) functional used here tends to overestimate the thermodynamic stability of noble-gas compounds, and that more accurate values can be generally achieved with the application of the hybrid HSE06 functional [30].…”
Section: Pressures Up To 50 Gpasupporting
confidence: 76%
See 1 more Smart Citation
“…In contrast, the experimental enthalpy of formation at ambient pressure is slightly positive (0.21 eV/atom [16]). This value was well reproduced with rigorous coupled-cluster calculations of Dixon et al [55]. In our previous study, we found that the Perdew-Burke-Ernzerhof (PBE) functional used here tends to overestimate the thermodynamic stability of noble-gas compounds, and that more accurate values can be generally achieved with the application of the hybrid HSE06 functional [30].…”
Section: Pressures Up To 50 Gpasupporting
confidence: 76%
“…In our previous study, we found that the Perdew-Burke-Ernzerhof (PBE) functional used here tends to overestimate the thermodynamic stability of noble-gas compounds, and that more accurate values can be generally achieved with the application of the hybrid HSE06 functional [30]. Indeed, calculation performed with the use of this functional gives ∆H f (KrF 2 ) = 0.06 eV/atom, much closer to the theoretical value of Dixon et al (0.21 eV/atom, [55]). However, the high computational cost of the HSE06 functional severely restricts the number of compounds that can be studied.…”
Section: Pressures Up To 50 Gpasupporting
confidence: 73%
“…It was in the outburst of genius that Bartlett decided to react xenon with a small sample of PtF 6 which resulted in the isolation of the first noble gas compound (Bartlett 1962), what proved to be a mixture of several distinct compounds (Bartlett et al 1976), as it was finally confirmed only half a century from the initial discovery (Graham et al 2000;Craciun et al 2010;Seppelt 2015). The noble gas chemistry-particularly that of xenon and krypton, and including organoxenon chemistry (Naumann and Tyrra 1989;Frohn and Jakobs 1989)-has flourished since 1962 (Christe and Wilson 1982;Christe et al 1991;Dixon et al 2007), and even argon has proved to form a stable chemical compound, HArF, at sufficiently low temperatures (Khriachtchev et al 2000)-it remains the only isolated chemical compound of argon. Consequently, with over half a thousand of currently known compounds of noble gases, their chemistry has been extensively reviewed during the last three decades (Laszlo and Schrobilgen 1988;Lehmann et al 2002;Schrobilgen and Moran 2003;Grochala 2007;Grochala et al 2011;Brock et al 2013;Hope 2013;Haner and Schrobilgen 2015).…”
mentioning
confidence: 99%
“…For the 19 F chemical shifts, the only exception for the calculated chemical shifts being larger than experiment is for SeF 6 2-where the trend is in the opposite direction and the calculated 19 F chemical shifts are more negative than experiment. This is no surprise because the free valence electron pair of Se is partially sterically active [8,49] requiring very high-level computations for reliable results [50][51][52][53]. The structures of the isoelectronic molecules KrF 6 and BrF 6 À are octahedral but the structures of XeF 6 and IF 6 À are C 3v with the octahedral structure slightly higher in energy.…”
mentioning
confidence: 99%